A systematic review of sinus floor augmentation complications. Does graft type influence the complications rate? - Ilinca Antigona Iancu; Stefania Andrada Iancu; Dragos Epistatu; Ioana Anca Badarau (Amaltea Medical Publishing House, 2023)
Background. Sinus floor elevation is considered a safe procedure to properly augment the height of the edentulous crest. Often, complications may arise due to multiple causes and can lead to a poor outcome of the graft and implant's osseointegration. A careful surgical approach, a good knowledge of possible obstacles, and careful treatment planning can reduce the risks of complications, as well as their impact on the surgical outcome. This study aims to make a literature review of 40 articles, analyzing the incidence and type of complications related to maxillary sinus graft surgeries and graft materials. Material and methods. A total of 40 articles published between 2015 and 2021 were selected for a systematic literature review on maxillary sinus floor complications. The studies were selected from 2 different internet databases: PubMed and Science Direct. The sinus lift complications were counted and their incidence was organized upon the surgical technique and the timing of occurrence (intraoperative, postoperative). It was also analyzed if the graft material influences the complication rate. Results. In a group of 1757 sinus augmentation surgeries performed on 1605 patients, 363 complications were found. Sinus membrane perforation occurred in 242 cases, 29 procedures resulted in partial or total graft loss, there were 26 postoperative cases of sinusitis, 24 sinus infections, 16 wound dehiscence, 6 bleeding complications, 5 lost implants, and 2 oro-antral fistulas. Conclusion. Sinus lift complications are sometimes inherent circumstances of the procedures, but they can also be prevented through an accurate technique and preoperative plan. The type of bone graft does not influence the incidence of surgical complications.